2014
DOI: 10.1186/1471-2229-14-110
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic analysis of grapevine leaves by iTRAQ reveals responses to heat stress and subsequent recovery

Abstract: BackgroundHigh temperature is a major environmental factor limiting grape yield and affecting berry quality. Thermotolerance includes the direct response to heat stress and the ability to recover from heat stress. To better understand the mechanism of the thermotolerance of Vitis, we combined a physiological analysis with iTRAQ-based proteomics of Vitis vinifera cv Cabernet Sauvignon, subjected to 43°C for 6 h, and then followed by recovery at 25/18°C.ResultsHigh temperature increased the concentrations of TBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 82 publications
8
84
0
Order By: Relevance
“…Besides, the abundance of PSI reaction center subunit VI was increased by heat stress. Previous studies indicated that PSI reaction center subunits III, N and VI were up-regulated by heat stress [27]. Our results here showed that PSI reaction center subunit VI interacted with sHSP26 and RNAimediated silencing of sHSP26 reduced the accumulation of oxygen-evolving enhancer protein 1.…”
Section: Shsp26 May Protect Photosynthesis Proteins Against Heat Stresssupporting
confidence: 64%
“…Besides, the abundance of PSI reaction center subunit VI was increased by heat stress. Previous studies indicated that PSI reaction center subunits III, N and VI were up-regulated by heat stress [27]. Our results here showed that PSI reaction center subunit VI interacted with sHSP26 and RNAimediated silencing of sHSP26 reduced the accumulation of oxygen-evolving enhancer protein 1.…”
Section: Shsp26 May Protect Photosynthesis Proteins Against Heat Stresssupporting
confidence: 64%
“…Wu et al (2015) investigated changes of fruit quality and protein expression profiles of grape berries upon hot water treatment during the subsequent 45 d of cold storage, finding immediate increased expression of proteins associated with carbohydrate and energy metabolism. Liu et al (2014) combined a physiological analysis with iTRAQ-based proteomics of cv Cabernet Sauvignon grape leaves subjected to 43°C stress for 6 h. They proposed that some proteins related to the electron transport chain of photosynthesis, antioxidant enzymes, HSPs, and other stress response proteins, as well as glycolysis, may play key roles in enhancing grapevine adaptation to and recovery capacity from heat stress. However, these transcriptomic and proteomic studies were not conducted on the same grape materials, so it is difficult to compare their results.…”
mentioning
confidence: 99%
“…Total protein was extracted using the cold acetone method (Liu et al 2014). Two biological replicates were carried out for each sample.…”
Section: Protein Extraction Digestion and Itraq Labelingmentioning
confidence: 99%
“…Among those proteins, 221 proteins were characterized as differentially expressed proteins, with at least two significant peptide sequences and an expression ratio[1.50 or\0.67 (Liu et al 2014;Wang et al 2013) under exogenous Spd or NaCl compared with the control and in Spd?NaCl-treated plants compared with NaCl alone (Supporting Information Table 1 and 2). Compared with the control, exogenous Spd treatment changed the abundances of 45 proteins: 40 proteins were increased and five were decreased.…”
Section: Protein Identification and Functional Classificationmentioning
confidence: 99%
See 1 more Smart Citation